Aspiration among the students of education college according to some variables "A field study in Tishreen University" - Kahileh, Reem; Baddour, lina; Trebosh, Ola (Latakia University Journal - Arts and Humanities Sciences Series, 2017)
Research was conducted on a sample of students in culture college in Tishreen University. Numbered (70) teenagers. The researcher used the Aspiration scale (prepared by the Ghazal Ahmad younes2015). The study aimed to identify: - The level of Aspiration among the students of culture college. - The difference between the study sample in Aspiration according to gender variable. - . The difference between the study sample in Aspiration according to place of residence variable. - . The difference between the study sample in Aspiration according branche of secondary school certificate variable. - Researcher found the following results: Aspiration level of the students of education college in Tishreen University, is located at the third level which is a high Aspiration. There is statistically significant difference between the study sample in Aspiration according to gender variable in favor of females. As such, there is statistically significant difference between the study sample in Aspiration according to place of residence variable in favor of villagers. There is no statistically significant difference between the study sample in Aspiration according to branche of secondary school certificate variable.